Applications of Radiation Chemistry in the Fields of Industry, Biotechnology and Environment - Venturi, Margherita; D'Angelantonio, Mila.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The series Topics in Current Chemistry Collections presents critical reviews from the journal Topics in Current Chemistry organized in topical volumes. The scope of coverage is all areas of chemical science including the interfaces with related disciplines such as biology, medicine and materials science. The goal of each thematic volume is to give the non-specialist reader, whether in academia or industry, a comprehensive insight into an area where new research is emerging which is of interest to a larger scientific audience. Each review within the volume critically surveys one aspect of that topic and places it within the context of the volume as a whole. The most significant developments of the last 5 to 10 years are presented using selected examples to illustrate the principles discussed. The coverage is not intended to be an exhaustive summary of the field or include large quantities of data, but should rather be conceptual, concentrating on themethodological thinking that will allow the non-specialist reader to understand the information presented. Contributions also offer an outlook on potential future developments in the field.
Radiation Induced Degradation of Organic Pollutants in Waters and Wastewaters -- Electron Beam Technology for Environmental Pollution Control -- Radiation Grafting for the Functionalization and Development of Smart Polymeric Materials -- Radiation Engineering of Multifunctional Nanogels -- Chitosan-Based Matrices Prepared by Gamma Irradiation for Tissue Regeneration: Structural Properties vs. Preparation Method -- Application of Radiation Chemistry to Some Selected Technological Issues Related to the Development of Nuclear Energy -- Upgrading and Refining of Crude Oils and Petroleum Products by Ionizing Irradiation -- The Use of Gamma Radiation for the Treatment of Cultural Heritage in the Argentine National Atomic Energy Commission: Past, Present, and Future -- Electron Beam Technology and Other Irradiation Technology Applications in the Food Industry -- Applications of Accelerators and Radiation Sources in the Field of Space Research and Industry.<.
Keywords: Nuclear chemistry; Radiation dosimetry; Chemistry, Technical; Biotechnology; Medical physics; Nuclear Chemistry; Radiation Dosimetry and Protection; Industrial Chemistry; Biotechnology; Medical Physics